Pulmonary Arterial Hypertension (PAH) Group 1 (Part A): Overview, Classification, Clinical Subsets, and Workup - Yaqoob, Maidah; DeCato, Thomas W.; Oudiz, Ronald (Current Respiratory Medicine Reviews, 2024)
Pulmonary hypertension is a rare, progressive disease characterized by increased pulmonary arterial pressure and right ventricular failure due to pulmonary vascular remodeling. The disease definition and management have evolved over time. The 6th WSPH now defines it as a mean pulmonary arterial pressure >20mmHg, while recent ESC/ERS guidelines recommend lowering the threshold for pulmonary vascular resistance to 2WU. Understanding of the disease has improved through registries, classifying it into five distinct groups with similar histology, pathophysiology, and therapeutic approaches. These groups include PAH, with heritable and idiopathic causes, as well as various clinical subsets involving connective tissue disease, HIV, portopulmonary hypertension, congenital heart disease, and schistosomiasis. Long-term responders to calcium channel blockers, PAH with venous/capillaries involvement, and persistent PH of newborns are categorized under Group 1, now re-classified as IPAH. A comprehensive workup for suspected patients includes various tests like electrocardiogram, pulmonary function testing, autoimmune workup, HIV testing, echocardiogram, right heart catheterization, and cardiopulmonary exercise testing. This review emphasizes the disease's definition and epidemiology, delving into each subset and providing updated workup guidelines. The subsequent article will focus on risk stratification and treatment strategies.
Keywords: Pulmonary arterial hypertension